Mass violence in individuals with Autism Spectrum Disorder and Narcissistic Personality Disorder: A case analysis of Anders Breivik using the "Path to Intended and Terroristic Violence" model. (November 2016) - Faccini, L.; Allely, C.S.
Abstract: Objective: There exist significant gaps in our understanding and knowledge of the contributory factors which give rise to the development of a mass shooter. Method: A case analysis is presented of Anders Behring Breivik who engaged in a bombing and shooting spree in Norway on July 22, 2011. Results: The case analysis presents that he has diagnoses of Asperger's Syndrome, Narcissistic Personality Disorder, and Antisocial Personality Traits/Disorder. Additionally, a forensic profile is presented that a narcissistic decompensation contributed to him developing a depression, followed by a rewrite of his life story where he is a hero defending Europe against a conspiracy. However his personal and political grievances and violent ideation placed him onto the Path to Intended/Terroristic Violence, which culminated in the attacks in Norway. Conclusions: The present study suggests that there may be an association between NPD and violence, similar to other studies. However, the factor of narcissistic decompensation (possibly co-occurring with an Asperger's coping strategy) was presented as a critical component of NPD that mediated its relationship with violence. Furthermore, aspects from his Asperger's Syndrome and Narcissistic Decompensation contributed to his personal and political grievances and the other steps on the Path towards Intended/Terroristic Violence. Highlights: Narcissism has been identified as existing in some shooter's profile. A facet of Narcissistic Personality Disorder (NPD), namely narcissistic decompensation is of central importance in understanding the path Breivik undertook in waging his personal and political "war". The present study suggests that there may be an association between NPD and violence, similar to other studies. The factor of narcissistic decompensation (possibly co-occurring with an Asperger's coping strategy) was presented as a critical component of NPD that mediated its relationship with violence in the case of Anders Breivik.